Hierarchical cobalt sulfide with vertical in-plane edge structure for enhanced electrocatalytic oxygen evolution reaction. (10th August 2018) - Lin, Ruijie; Lin, Tongxi; Huang, Junying; Huang, Xiaohui; Liu, Yingju
Abstract: Transition metal-based sulfides are hopeful nonprecious eletrocatalysts for enhanced oxygen evolution reaction (OER). Compared with noble-metal based materials, such transition metal-based sulfides have been widely investigated in catalysis and energy storage, which can be easily controlled into various morphology due to their various valences. However, it is still a challenge to engineer transition metal-based sulfides of 3D nanostructure with rich edges. In this work, hierarchical cobalt sulfide nanocomposites (HCSN), with the vertical growth of Co9 S8 nanosheets on horizontal Co1-x S nanoplates, were fabricated via simple one-pot synthesis. Due to adequate exposed-edge planes, the HCSN exhibited remarkably catalytic property for OER with low overpotential of 275 mV at a current density of 10 mA cm −2, a low Tafel slope of 30 mV/decade and excellent stability. By investigating the chemical states before and after OER, the possible catalytic mechanism was provided. This work may provide a simple and efficient method to prepare hierarchical metal sulfides for electrocatalytic OER. Graphical abstract: Image 1 Highlights: A direct growth of hierarchical Co1-x S/Co9 S8 nanostructure was formed and characterized. It exhibited remarkable OER activity with Tafel slope of 30 mV per decade. A possible catalytic mechanism of such hierarchical cobalt sulfide was put forward.